Emerging drugs for urothelial (bladder) cancer. (3rd April 2017) - Cumberbatch, Kerwin; He, Tianfang; Thorogood, Zachary; Gartrell, Benjamin A
ABSTRACT: Introduction : Metastatic urothelial carcinoma has been associated with poor prognosis and a median survival of approximately 12–14 months with standard therapy. Treatment options for decades have been limited to platinum based chemotherapy as first line with few therapeutic options available to the majority who will ultimately progress beyond platinum. Areas covered : This review focuses on the various targeted, antiangiogenic, chemotherapeutic and immunotherapeutic agents currently being developed for the treatment of urothelial carcinoma. Expert opinion : Incorporation of systemic immunotherapy into the treatment of urothelial carcinoma has already fundamentally changed the treatment of this disease. The landscape is rapidly changing and it is likely that immunotherapy will be incorporated into therapy in earlier disease states and in novel combinations. Outcomes in urothelial carcinoma have improved and likely to improve further with ongoing and future clinical research that is discussed in this review.